2022
DOI: 10.1109/jbhi.2022.3172994
|View full text |Cite
|
Sign up to set email alerts
|

Effective Connectivity in Cortical Networks During Deception: A Lie Detection Study Based on EEG

Abstract: Previous studies have identified activated regions associated with deceptive tasks and most of them utilized time, frequency, or temporal features to determine deceptive responses. However, when deception behaviors occur, the functional connectivity pattern and the communication between different brain areas remain largely unclear. In this study, we explored the most important information flows between different brain cortices during deception. First, we employed the guilty knowledge test protocol and recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Other studies have found that enhanced communication between the 44R and 45L brain regions is associated with an increased working memory load during the act of lying [14,58]. The 44R region has been identified as a key "hub" in connectivity networks, potentially reflecting brain activity related to episodic memory and new information encoding [59]. The BA 9R/10R regions have been linked to strategic processes in memory recall, recognition, and various executive functions, and the BA44 region has been implicated in selective response suppression in go/no-go tasks [60].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that enhanced communication between the 44R and 45L brain regions is associated with an increased working memory load during the act of lying [14,58]. The 44R region has been identified as a key "hub" in connectivity networks, potentially reflecting brain activity related to episodic memory and new information encoding [59]. The BA 9R/10R regions have been linked to strategic processes in memory recall, recognition, and various executive functions, and the BA44 region has been implicated in selective response suppression in go/no-go tasks [60].…”
Section: Discussionmentioning
confidence: 99%
“…After applying the first step of filter‐based feature selection, an OFS was created using a wrapper strategy (see Figure 3B) for feature selection 29,30 . First, TFS in each microstate was ranked based on mRMR, and the top‐ranked new features were gradually added to the feature space to form a new feature vector.…”
Section: Methodsmentioning
confidence: 99%
“…After applying the first step of filter‐based feature selection, an OFS was created using a wrapper strategy (see Figure 3B ) for feature selection. 29 , 30 First, TFS in each microstate was ranked based on mRMR, and the top‐ranked new features were gradually added to the feature space to form a new feature vector. Then, a five‐fold cross‐validation (CV) strategy was applied to the ranked TFS, with the samples randomly divided into a training dataset (Dtra) and a testing dataset (Dtes) in a 4:1 ratio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of Labkovsky et al [15] demonstrated that the false positive rate of deception detection utilizing P300 remains significant. Based on this, researchers used nonlinear analysis techniques to extract features from multi-channel ERP and machine learning to identify and classify features, which not only facilitates further decoding of the information processing mechanism of the brain during deception, but also further improves the accuracy of deception detection [2], [16], [17].…”
Section: Introductionmentioning
confidence: 99%